The construction and reconstruction of ESL student teachers’ professional identity - Raja Nor Safinas Raja Harun (Universitas Syiah Kuala, 2019)
This study explores the construction and reconstruction of ESL student teachers’ professional identity at a teacher education university in Malaysia. A number of 23 student teachers were required to upload a journal entry in the e-portfolio to reflect upon themselves as prospective teachers when they were doing a pedagogical course in semester 5. Upon completing their teaching practice in semester 7 and while doing seminar reflective as a course in their final semester, the student teachers were asked to revisit their journal entry on their identity and to compare and contrast if their views have changed or remained the same after their teaching practice experiences. A content analysis was used to study the transformation of identity through journal entries. The study reveals that the student teachers were more realistic and practical as opposed to being idealistic in forming their professional identities after the teaching practice. There were many situational factors which have affected such changes. This study implicates the need for teacher education programs to provide platforms and learning to teach experience that would assist the student teachers formation of professional identity as prospective teachers.